An evaluative investigation into double-bay carports comparing current design practices with the specifications of the codes of practice - Van der Merwe, Rufus Roche (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1994.